Pengaruh pelatihan kerja dan promosi jabatan terhadap kinerja karyawan pt badak ngl bontang - Renaldi Basudewa; Zainal Ilmi; Dirga Lestari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
Renaldi Basudewa. 2018. The influence of Job Training and Job Promotion on Employee Performance in PT. Badak NGL Bontang. Guidance of Mr. Zainal Ilmi as first counsellor and Mrs. Dirga Lestari as second counsellor. The purpose of this study was to determine the influence of Job Training and Job Promotion on Employee Performance. The method used is the sampling technique and census. The sample in this study were 33 respondents. Data analysis method in this study is Multiple Linier Regression using SPSS version 21. The result of this study show that: Job Trainng influence on performance evidenced by output where the value tarithmetic ttable (2,712 1,310) with significant value 0,011  0,05. Job Promotion has a significant influence on performance evidenced by output where the value tarithmetic ttable (2,928 1,310) with significant value 0,006 0,05. Job Training and Job Promotion  together has a positive and significant influence on performance, the results evidenced by output where the value Farithmetic23,241 with significant level 0,000. Because value Farithmetic resulting bigger than Ftabel (3,32) and the significant of the resulting value is smaller than 0,05